Baseline Red Blood Cell Distribution Width as a Predictor of Stroke Occurrence and Outcome: A Comprehensive Meta-Analysis of 31 Studies - Song, Si-Ying; Hua, Chang; Dornbors, David; Kang, Rui-jun; Zhao, Xiao-Xi; Du, Xin; He, Wen; Ding, Yu-chuan; Meng, Ran (Frontiers in Neurology, 2019)
Background: Red blood cell distribution (RDW) may be a potential biomarker of inflammation in patients with stroke. Elevated RDW is associated with higher incidence of stroke, unfavorable functional outcome and increased mortality, although results are inconsistent in the reported literature. This study aims to evaluate the predictive power of RDW regarding stroke occurrence and outcome. Methods: A thorough literature search was conducted utilizing the PubMed Central (PMC) and EMBASE databases to identify studies up to May 2019. Data from these studies was pooled, and combined odds ratios/risk ratios (ORs/RRs) were estimated for the risk of stroke, functional outcome and mortality. Subgroup analysis was also performed to explore heterogeneity in terms of population status, demographic factors (age, gender distribution, and country), and vascular risk factors (hypertension, diabetes mellitus and current smoking). Results: A total of 31 studies with 3,487,896 patients were included in the analysis. Elevated RDW was found to be a risk factor in ischemic stroke (OR 1.528; 95% CI 1.372-1.703), while combined OR in subarachnoid hemorrhage (SAH) was not statistically significant (OR 1.835; 95% CI 0.888-3.792). Elevated RDW posed increased risk in populations with conventionally higher risk of stroke, such as atrial fibrillation (AF) (OR 1.292; 95% CI 1.107-1.508) and diabetes mellitus (OR 2.101; 95% CI 1.488-2.968), and in community cohorts (OR 1.245; 95% CI 1.216-1.275). In addition, higher RDW was associated with unfavorable functional outcome, either at discharge (OR 1.220; 95% CI 1.070-1.39) or at 90 days (OR 1.277; 95% CI 1.155-1.413). Higher mortality was found in patients with increased RDW (OR 1.278; 95% CI 1.221-1.337), independent of demographic factors (age, gender distribution, country). Conclusions: Baseline RDW should be integrated into clinical practice as a predictor of ischemic stroke occurrence and outcome. Future studies should also explore the dynamic change of RDW in post-stroke patients to evaluate the clinical significance of RDW and its impact on the inflammatory state of ischemic stroke.